PTH-003 Outcomes following endoscopic mucosal resection (emr) of colonic polyps in a tertiary centre: a three year experience. (22nd June 2015) - Nesargikar, P; Amadio, L; Noble, C; Wilson, G; Potter, M
Abstract : Introduction: EMR for large sessile and flat colonic polyps has minimised the need for surgical intervention with acceptable outcomes. The aim of this study was to evaluate the indications, outcomes, complications and recurrence rates following EMR. Method: Patients who underwent EMR over a three year period from 2011 to 2014 were analysed retrospectively for technique, polyp characteristics, pathology, recurrence rates and complications. Results: Eighty EMRs were carried out over a 3 year period (male:female 52:28, mean age 68.25 yrs). The median polyp size was 28.5 mm (range 10 mm–60 mm). The most common sites of EMR were rectosigmoid (36%), caeum (27.5%) and ascending colon (17.5%). Only two polyps failed to be lifted, with majority of polyps retrieved piecemeal. Tubolovillous adenomas (75%) were the predominant histological pattern, with low grade dysplasia present in 10% (8/80), high grade dysplasia in 27.5% (22/80) and polyp cancers in 3.75% (3/80) of patients. Early follow up was at a median of 5 months, with further endoscopic review determined by BSG guidelines. Polyp recurrence rate at the site of original EMR was 17.5%. All were successfully treated endoscopically. Complications included bleeding (n = 4), abdominal pain (n = 1), post polypectomy syndrome (n = 1) and perforation (n = 1). Of these 7 patients, two patients required operative intervention and rest were managed conservatively. APC was used in 64% patients and was associated with 6 of the above 7 complications. Conclusion: This study is one of the bigger studies reported in UK to date, and we have shown that EMR is a safe procedure with few complications and acceptable recurrence rates. The most significant complication of perforation was encountered in the early days of EMR. This study demonstrates that with experience on the learning curve, EMR can be safely practiced and advocated for large colonic polyps. Disclosure of interest: None Declared. References: Repici A et al . Endoscopic mucosal resection for early colorectal neoplasia: pathologic basis, procedures, and outcomes. Dis Colon Rectum 2009;52 :1502–15 Seitz U et al . Is endoscopic polypectomy an adequate therapy for malignant colorectal adenomas? Presentation of 114 patients and review of the literature. Dis Colon Rectum 2004;47(11):1789–96 Carvalho R et al . Endoscopic mucosal resection of large colorectal polyps: prospective evaluation of recurrence and complications. Acta Gastroenterol Belg 2013;76 :225–30